Direct and correlated responses to single trait selection in a crossbred poultry flock - Larrambebere, Walter Heber Saralegui (Pesquisa Agropecuaria Brasileira, 2014)
A cross population was formed between 1957/1961 by crossing together four breeds of poultry (Gallus domesticus): Rhode island Red, Light Sussex, Brown Leghorn and White Leghorn. The object was to try to increase the additive genetic variance for egg production and then to exploit this by means of a single trait selection programme. The results of seven generations have been described. The birds were reared on deep litter and housed in single bird laying cages from 19-68 weeks of age. Attempts were made to keep the environmental conditions uniform for all the birds, throughout this period. The size of the populations was approximately 1.400 pullets caged each year from 60 sires and about 180 dams. Selection was based solely on partial egg production, to approximately 40 weeks. Combined individual plus weighted full sib information was used to select females, and weighted full sib information only for males. Each year a sample of pullets resulting from matings between two pedigreed control strains was obtained from a breeding company. These control birds were reared from day-old with the selection lines pullets. The egg production of the control declined significantly during six generations, and this was attributable both to an increased age at maturity and a decreased rate of lay. Egg and body weights remained comparatively stable. The control adjusted changes were taken as the best estimates of the genetic changes caused by selection.